Comparative Analysis of Financial Performance Before and After the Acquisition (Study on the Go Public Acquisitors For The Period of 2011-2019) - Amalia Nur Masita; Maria Theresia Heni Widyarti; Tutik Dwi Karyanti; Alvianita Gunawan Putri (Ilomata International Journal of Management, 2022)
The study aims to compare financial performance in Go Public Acquirer Companies before and after acquisition by analyzing significant differences in related to Liquidity (Current Ratio and Quick Ratio), Solvency (Debt to Asset Ratio and Debt to Equity Ratio), Activity (Total Asset Turn Over) and Profitability (Return on Assets, Return on Equity, and Net Profit Margin). This study used secondary data of financial statements two years before and after the acquisition of the acquirer company 2013-2017 with the research period of 2011-2019. The sampling technique use purposive sampling. A hypothesis test tool for testing H1 until H8 using Paired Sample T-Test or Wilcoxon Signed Rank Test. The results showed that there is a significant difference in Debt to Equity Ratio, Total Asset Turn Over, Return on Assets, Return on Equity, dan Net Profit Margin, while in Current Ratio, Quick Ratio, and Debt to Asset Ratio there is no significant difference.